Appendectomy surgical technique and surgical site infection. Hospital María Auxiliadora. October – December 2018 - Sandoval Gionti, Ursula Alexandra (2019)
Objective: To determine the incidence and factors associated with surgical site infection in patients who underwent an appendectomy in the General Surgery Unit of the Hospital María Auxiliadora from October to December 2018. Materials and methods: A cross-sectional comparative-case study was conducted in a historical cohort of patients who underwent an appendectomy during the study period. Data was obtained from medical records of patients who underwent surgery using three surgical techniques (transverse, transumbilical and laparoscopic appendectomy). Surgical site infection, clinical demographic characteristics and factors associated with the development of this complication were determined. Results: Twenty percent (20 %) of the patients who underwent an appendectomy presented surgical site infection, mostly those operated with the transverse surgical technique (56 %) (p = 0.03) and those with complicated appendicitis (54 %) (p < 0.001), who required a longer hospital stay of 4 days (IQR: 2-6) (p < 0.01). A multiple regression analysis showed an association between surgical technique (transumbilical and transverse appendectomy) and surgical site infection [IRR: 3.72; 95 % CI (1.58-8.75) and 2.63 95 % CI (1.27-5.44)] and development of complicated appendicitis [IRR: 5.56 95 % CI (2.32-13.35). Conclusions: Surgical site infection is a frequent complication of appendectomy and is associated with the surgical technique and complicated appendicitis.